2004
DOI: 10.1093/nar/gkh256
|View full text |Cite
|
Sign up to set email alerts
|

A programmed -1 ribosomal frameshift signal can function as a cis-acting mRNA destabilizing element

Abstract: Nonsense-mediated mRNA decay (NMD) directs rapid degradation of premature termination codon (PTC)-containing mRNAs, e.g. those containing frameshift mutations. Many viral mRNAs encode polycistronic messages where programmed -1 ribosomal frameshift (-1 PRF) signals direct ribosomes to synthesize polyproteins. A previous study, which identified consensus -1 PRF signals in the yeast genome, found that, in contrast to viruses, the majority of predicted -1 PRF events would direct translating ribosomes to PTCs. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 32 publications
0
36
1
Order By: Relevance
“…Similarly, it has been proposed that in mammalian cells, NMD occurs only during a pioneer round of translation (Lejeune et al 2004). In contrast, studies in both yeast and rats have shown a decrease in RNA levels due to an infrequently translated PTC (Buzina and Shulman 1999;Plant et al 2004). This is not surprising since RNAs in yeast can undergo NMD during any round of translation (Maderazo et al 2003).…”
Section: Possible Nmd Mechanisms For Rsv Rnamentioning
confidence: 98%
“…Similarly, it has been proposed that in mammalian cells, NMD occurs only during a pioneer round of translation (Lejeune et al 2004). In contrast, studies in both yeast and rats have shown a decrease in RNA levels due to an infrequently translated PTC (Buzina and Shulman 1999;Plant et al 2004). This is not surprising since RNAs in yeast can undergo NMD during any round of translation (Maderazo et al 2003).…”
Section: Possible Nmd Mechanisms For Rsv Rnamentioning
confidence: 98%
“…If a uORF (upstream ORF) is translated by the ribosome, its TC could be regarded as premature due to the bulk of the downstream sequences that separate stop codon position from poly(A) tail as well as due to possible downstream intron(s). Furthermore, programmed frameshifts, selenocysteineencoding UGA codons, and leaky scanning initiation codons can target transcripts for NMD (Moriarty et al 1998;Welch and Jacobson 1999;Plant et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Although it is relatively rare, Ϫ1 PRF has also been documented to occur in prokaryotes (Escherichia coli dnaX gene), with just one instance of Ϫ1 PRF clearly shown to occur in mammalian cells (Edr gene) (12). Recent findings suggest that Ϫ1 PRF might be used in Saccharomyces cerevisiae to endogenously posttranscriptionally regulate gene expression by targeting mRNAs containing premature termination codons for nonsensemediated mRNA decay (13).…”
mentioning
confidence: 99%